Model Keputusan Konsumen Penggunaan Self-Collection Parcel Locker Untuk Last Mile Delivery - Muhammad Iqbal Firdaus; Riza Lestari; Sarovah Widiawati (Institut Transportasi dan Logistik Trisakti, 2021)
Last mile delivery is the most inefficient part of the total consumer goods delivery process due to the high rate of return, segmented goods and relatively small quantity. One of the innovations made by e-retailers and logistics service providers is to install self-collection parcel lockers in easily accessible places where the process of picking up goods is carried out independently by consumers in these places. There are not many studies conducted to identify what factors can encourage consumers to use these services, focusing more on cognitive attitudes, segmented and the results are still inconclusive. This study aims to investigate that utilitarian, hedonic, situational and social factors influence consumer decisions to use parcel locker self-collection services. This survey quantitative study used non-probability sampling technique and succeeded in obtaining 264 samples. The analysis tool uses Structural Equation Modeling with a covariance-based approach with AMOS. The results show that the customization by consumers according to their preferences is a factor that influences consumers' intention to use self-collection parcel locker services along with utilitarian motives